(untitled) (Human Computation, 2021)
This paper reports outcomes of a systematic scoping review of methodological approaches and analytical lenses used in empirical research on crowdwork. Over the past decade a growing corpus of publications spanning Social Sciences and Computer Science/HCI have empirically examined the nature of work practices and tasks within crowdwork; surfaced key individual and environmental factors underpinning workers’ decisions to engage in this form of work; developed and implemented tools to improve and extend various aspects of crowdwork, such as the design and allocation of tasks and incentives or workflows within the platforms; and contributed new techniques and know-how on data collection within crowdwork, for example, how to conduct large-scale surveys and experiments in behavioural psychology, economics or education drawing on crowdworker samples. Our initial reading of the crowdwork literature suggested that research had relied on a limited set of relatively narrow methodological approaches, mostly online experiments, surveys and interviews. Importantly, crowdwork research has tended to examine workers’ experiences as snapshots in time rather than studying these longitudinally or contextualising them historically, environmentally and developmentally. This piece-meal approach has given the research community initial descriptions and interpretations of crowdwork practices and provided an important starting point in a nascent field of study. However, the depth of research in the various areas, and the missing pieces, have yet to be systematically scoped out. Therefore, this paper systematically reviews the analytical-methodological approaches used in crowdwork research identifying gaps in these approaches. We argue that to take crowdwork research to the next level it is essential to examine crowdwork practices within the context of both individual and historical-environmental factors impacting it. To this end, methodological approaches that bridge sociological, psychological, individual, collective, online, offline, and temporal processes and practices of crowdwork are needed. The paper proposes the Life Course perspective as an interdisciplinary framework that can help address these gaps and advance research on crowdwork. The paper concludes by proposing a set of Life Course-inspired research questions to guide future studies of crowdwork.